2000
DOI: 10.4049/jimmunol.165.9.4870
|View full text |Cite
|
Sign up to set email alerts
|

Graded Deletion and Virus-Induced Activation of Autoreactive CD4+ T Cells

Abstract: We have examined factors governing the negative selection of autoreactive CD4+ T cells in transgenic mice expressing low (HA12 mice) vs high (HA104 mice) amounts of the influenza virus hemagglutinin (HA). When mated with TS1 mice that express a transgenic TCR specific for the I-Ed-restricted determinant site 1 (S1) of HA, thymocytes expressing high levels of the clonotypic TCR were deleted in both HA-transgenic lineages. However, through allelic inclusion, thymocytes with lower levels of the clonotypic TCR eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…HA104 mice express high levels of the HA Ag in all tissues whereas HA28 mice have been found to express lower levels. When TS1 mice are crossed with HA104 mice, the resulting double transgenic progeny delete the majority of all 6.5-expressing thymocytes (25). In contrast, (TS1 ϫ HA28)F 1 mice delete few of these cells, and rather have a peripheral repertoire characterized by large numbers of 6.5 ϩ CD4 T cells with an immunoregulatory phenotype (CD25 ϩ CD45RB int ) (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HA104 mice express high levels of the HA Ag in all tissues whereas HA28 mice have been found to express lower levels. When TS1 mice are crossed with HA104 mice, the resulting double transgenic progeny delete the majority of all 6.5-expressing thymocytes (25). In contrast, (TS1 ϫ HA28)F 1 mice delete few of these cells, and rather have a peripheral repertoire characterized by large numbers of 6.5 ϩ CD4 T cells with an immunoregulatory phenotype (CD25 ϩ CD45RB int ) (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, thymic self-tolerance in TS1 mice expressing HA as a "neo-self Ag" has been extensively studied (20,24,25) and has revealed the participation of multiple pathways of self-tolerance, including the development of CD4 ϩ CD25 ϩ T cells that demonstrate potent immunoregulatory activity. We hypothesized that such a population of immunoregulatory cells might also contribute to the tolerant state induced by central Ag exposure via intrathymic injection of Ag and may provide a valuable component of protocols designed to achieve transplantation tolerance.…”
mentioning
confidence: 99%
“…However, thymocytes can also undergo deletion in response to selfpeptides (28,(32)(33)(34)(35)(36) and the relationship between CD25 ϩ T cell selection and deletion of autoreactive thymocytes remains poorly understood. In the studies here, TS1x␤-myoHA mice were found to contain significantly fewer 6.5 high CD4 SP thymocytes than TS1xPevHA and TS1xHA28 mice, although in all cases similar percentages (ϳ30%) were CD25…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we wanted to exclude the possibility that enhanced deletion of thymocytes expressing high levels of the 6.5 TCR caused the residual 6.5 high CD4 SP thymocytes in TS1x␤-myoHA mice to contain elevated numbers of CD25 ϩ thymocytes that coexpressed endogenous TCR ␣-chains (4,16,28). Accordingly, additional chimeras were generated using BM obtained from TS1.RAG mice and irradiated ␤-myoHA and BALB/c recipients.…”
Section: Radioresistant Elements Direct Enhanced Deletion and Cd4mentioning
confidence: 99%
“…Andy Caton, who came from England to join the Gerhard group, created transgenes of a T cell receptor that recognizes the HA 111-119 epitope, leading to establishment of a powerful system to study self-T cell responses. (13) Laurence ''Ike'' Eisenlohr based his doctoral research, performed in my lab at Wistar, and many excellent discoveries in his career, on understanding the mechanism by which these distinct influenza helper T cell epitopes are presented to T cells. (14) I am indebted to Hilary Koprowski for his vision, and to Walter Gerhard and the ''braintrust'' of all of our Wistar colleagues in viral immunology for their insightful, intelligent, and critical discussions and for their helping hands that channeled this research along a pathway that continues to pay dividends.…”
mentioning
confidence: 99%